1978
DOI: 10.1111/j.1365-2265.1978.tb03578.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Effects of Spironolactone in Man

Abstract: A double blind, controlled study was carried out in order to investigate the effects of administering spironolactone, 200 mg daily, to five healthy male volunteers. The patterns of change in plasma testosterone (T) and luteinizing hormone (LH) after spironolactone were significantly different from placebo and there were significant increases in the urinary excretion of androsterone (A), aetiocholanolone (EC) and total oestrogen. Urinary dehydroepiandrosterone (DHA) excretion, after an initial rise, declined pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Spironolactone has been reported to ameliorate hirsutism and decrease serum DHEA-S concentrations in women. 92 In healthy men 93 and in men with prostatic carcinoma, 94 it decreased concentrations of DHEA as well as testosterone and androstenedione. Other studies have not shown changes in DHEA and/or DHEA-S concentrations, potentially because of small sample size, 95,96 or the previous administration of dexamethasone to decrease steroid concentrations.…”
Section: Spironolactonementioning
confidence: 98%
“…Spironolactone has been reported to ameliorate hirsutism and decrease serum DHEA-S concentrations in women. 92 In healthy men 93 and in men with prostatic carcinoma, 94 it decreased concentrations of DHEA as well as testosterone and androstenedione. Other studies have not shown changes in DHEA and/or DHEA-S concentrations, potentially because of small sample size, 95,96 or the previous administration of dexamethasone to decrease steroid concentrations.…”
Section: Spironolactonementioning
confidence: 98%
“…Since over 80% of administered spironolactone is irreversibly converted to canrenone/canrenoic acid, its much higher anti-androgen activity on radioreceptor assay and bioassay may point to the generation of unidentified, minor metabolites with very high affinity for androgen receptors and/or a very long plasma half-life.Spironolactone is widely used as a potassium-sparing diuretic, although chronic highdose therapy can lead to side effects such as gynaecomastia and menstrual disorders (Stripp et al. 1975;Huffman et al, 1978;Tidd et al, 1978). The pathogenesis of these sideeffects is not completely understood.…”
mentioning
confidence: 99%
“…Spironolactone is widely used as a potassium-sparing diuretic, although chronic highdose therapy can lead to side effects such as gynaecomastia and menstrual disorders (Stripp et al. 1975;Huffman et al, 1978;Tidd et al, 1978). The pathogenesis of these sideeffects is not completely understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It retains *a weak progestational activity (183), and, as recent re-"ports suggest, an antiestrogenic effect (184). The administration of S-Fin man results in a number of hormonal changes such as transient rise of plasma total T and urinary DHA, followed by an increase of LH secretion (185). A significant increase in urinary excretion of estrone (Ei) and estriol (E 3 ) and a significant rise in plasma fevels of progesterone and 17-hydroxyprogesterone have 'also been reported (186,187).…”
Section: Management Of Hirsutism With Spmentioning
confidence: 97%